2022
DOI: 10.1037/ccp0000759
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted digital mental health interventions for ethnic/racial minorities: A systematic review and meta-analysis.

Abstract: Objective: Digital mental health interventions (DMHIs) are typically designed as “one-size fits all” which may perpetuate health disparities for racialized minorities. This systematic review identified culturally adapted DMHIs and examined their efficacy and acceptability among racial and ethnic minorities. Method: PsycINFO, Web of Science, and Pubmed databases were searched between 2000 and 2021. Studies that examined the development or impact of a culturally adapted DMHI for racial or ethnic minority populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…One of the main findings that this work highlights is the importance of the application Two-Eyed Seeing approach in Design Thinking and Indigenous storytelling to create culturally revitalizing digital mental health screening tools. The results of the current study are supported by Ellis and colleagues’ 2020 [ 39 ] meta-analytic study findings that showed culturally adapted eMental health interventions contributed to positive health outcomes among racial and ethnic minority communities. In particular, their meta-analysis highlighted that culturally safe eMental health interventions lessened mental illness symptoms and improved quality of life [ 39 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One of the main findings that this work highlights is the importance of the application Two-Eyed Seeing approach in Design Thinking and Indigenous storytelling to create culturally revitalizing digital mental health screening tools. The results of the current study are supported by Ellis and colleagues’ 2020 [ 39 ] meta-analytic study findings that showed culturally adapted eMental health interventions contributed to positive health outcomes among racial and ethnic minority communities. In particular, their meta-analysis highlighted that culturally safe eMental health interventions lessened mental illness symptoms and improved quality of life [ 39 ].…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current study are supported by Ellis and colleagues’ 2020 [ 39 ] meta-analytic study findings that showed culturally adapted eMental health interventions contributed to positive health outcomes among racial and ethnic minority communities. In particular, their meta-analysis highlighted that culturally safe eMental health interventions lessened mental illness symptoms and improved quality of life [ 39 ]. We found that Indigenous storytelling underpinned all aspects of design usability preferences for eMental health screening tools.…”
Section: Discussionsupporting
confidence: 82%
“…To the authors’ knowledge, this is the first large-scale outcomes evaluation of a culturally responsive video BCT program across racial and ethnic groups. Prior meta-analyses have reported greater effects for culturally adapted psychological interventions compared to unadapted or no psychological intervention among communities of color [ 44 , 45 ], including culturally-adapted internet-based psychological interventions [ 17 ]. However, unlike the BCT program evaluated in the current study, most of the interventions included in those analyses were adapted for specific racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, outcomes research of internet-based mental health interventions has primarily been conducted in samples that under-represent communities of color [ 14 ], and racial and ethnic differences in clinical outcomes of these interventions are not commonly evaluated. Studies of tele-counseling interventions and internet CBT (iCBT) have reported positive anxiety and depression treatment outcomes among communities of color [ 15 17 ]. However, most of this research has been limited by small sample sizes or has evaluated programs targeting specific racial and ethnic groups, increasing the difficulty in fully grasping the impact of large-scale interventions that aim to successfully treat diverse populations.…”
Section: Introductionmentioning
confidence: 99%
“…Most focus on people of diverse race/ethnicity, with two focusing specifically on Black/African American people and two on Latinx people. The majority of the articles address the development, acceptability, and/or efficacy of culturally adapted and culturally relevant interventions (Ellis et al, 2022; Bauer et al, 2022; Haft et al, 2022; Kaur et al, 2022; Singla et al, 2022; Sweeney et al, 2022; Wendt et al, 2022). The others address issues related to access to services (Joiner et al, 2022; López et al, 2022), treatment moderators (Patriarca et al, 2022), and effectiveness in the community (Joiner et al, 2022).…”
mentioning
confidence: 99%